Soil Erodibility Characteristics under Different Land Uses in Bundelkhand - Lal, B.; Biswas, H.; Raj, Sant (Indian Journal of Agroforestry, 2020)
A study was conducted to work out the soil erodibility characteristics under different land uses viz. agriculture, pastoral, si lvi-pastoral and forest existing in the Research Farm of Central Soil and Water Conservation Research and Training Institute, Research Centre, Datia (M.P.). Soil samples from (0-15 cm) were collected from 191 hectare catchment under different land uses. They were subjected to different analysis for various soil properties and different erodibility indices were worked out. The soil pH varied from 6.79 - 8.91. While bulk density was highest under forest land use; the soil was low in organic carbon content. Mean clay content varied from 12.0 per cent in forest to 17.5 under pastoral land use. Suspension percentage varied from 7.15 to 14.30 with highest value under forest land use’ indicating the highly erodible nature of these soils. Minimum erosion ratio was recorded under pastoral land use followed by silvi-pastoral, agriculture and forest which again confirmed the high erodibility of soils under the latter. Erosion ratio was significantly correlated with suspension percentage and dispersion ratio under agriculture, pastoral as well as silvi-pastoralland uses. Clay/moisture equivalent ratio has shown significant and indirect relationship with the erosion ratio under the land uses.